The faecal metabolome and mycobiome in Parkinson's disease. (February 2022) - De Pablo-Fernandez, Eduardo; Gebeyehu, Gerum Gashaw; Flain, Luke; Slater, Rachael; Frau, Alessandra; Ijaz, Umer Zeeshan; Warner, Thomas; Probert, Chris
Abstract: Background: Gut fungal composition and its metabolites have not been assessed simultaneously in Parkinson's disease (PD) despite their potential pathogenic contribution. Objective: To evaluate the faecal metabolome and mycobiome in PD by assessing volatile organic compounds (VOCs) and fungal rRNA. Methods: Faecal VOCs from 35 PD patients and two control groups (n = 35; n = 15) were assessed using gas chromatography and mass spectrometry. DNA was extracted from 44 samples: 18S rRNA gene amplicons were prepared and sequenced. Metabolomics, mycobiome and integrated analyses were performed. Results: Several VOCs were more abundant and short chain fatty acids were less abundant in PD. Hanseniaspora, Kazachstania, uncultured Tremellaceae and Penicillium genera were more abundant, and Saccharomyces less abundant in PD (FDR<0.0007). Torulaspora was associated with PD and two VOCs. Conclusion: PD patients had a distinct metabolome and mycobiome suggesting that fungal dysbiosis may contribute to PD pathogenesis. Highlights: Gut dysbiosis in Parkinson's may not be restricted to bacterial microbiome. Parkinson's patients have distinct mycobiome composition (fungal rRNA). Parkinson's patients have distinct faecal metabolome (volatile organic compounds). Faecal fungal dysbiosis may have a pathogenic role in Parkinson's disease.